PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR GEOGRAFI MATERI MOBILITAS PENDUDUK KELAS XI IPS SMA PERTIWI 1 PADANG - Harahap, Muhammad Ranto; Suasti, Yurni (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
Abstract This study aims to determine the effect of the problem-based learning model on the results of studying geography on population mobility in class XI IPS SMA Pertiwi 1 Padang. This type of research is quantitative based on quasi-experimental design experiments. Sampling used simple random sampling, namely the sample was taken randomly from the population so as to produce two sample groups for class XI IPS 1, the experimental group and class XI IPS 2, the control group. Student learning outcomes were obtained from the pretest and posttest before after treatment. The data analysis technique uses the t-test and normalized gain test. The results showed that tcount ≥ ttable with a significant level of 5% (0.05), namely 4.33 ≥ 1.99 so Ha was accepted and H0 was rejected. Then the normalized gain test N gain score of the experimental group is 0.72 with a high interpretation, while the control group is 0.46 with a moderate interpretation. So it can be concluded that there is an influence of the problem based learning model on geography learning outcomes. Keywords: Problem Based Learning, Experiments, Learning Outcomes